2014
DOI: 10.12659/msm.889924
|View full text |Cite
|
Sign up to set email alerts
|

To clarify features of photoplethysmography in monitoring balanced anesthesia, compared with Cerebral State Index

Abstract: BackgroundAlthough photoplethysmography and cerebral state index (CSI) have been used as indices in monitoring vital signs perioperatively, there are only a few reports comparing the performance of photoplethysmography with CSI in monitoring anaesthesia depth. The aim of the present study was to clarify features of photoplethysmography in monitoring balanced general anesthesia compared with CSI.Material/MethodsForty-five patients undergoing elective operation under general anaesthesia were enrolled in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Most of the previous studies utilized only the AC component of PPG [ 1 4 , 6 9 , 15 17 ]. However, the DC component of PPG is also known to change in response to vasoconstriction and vasodilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous studies utilized only the AC component of PPG [ 1 4 , 6 9 , 15 17 ]. However, the DC component of PPG is also known to change in response to vasoconstriction and vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous clinical studies that have used PPG-derived variables to evaluate the effects of nociception on autonomic responses have used only the AC component of PPG [ 1 4 , 6 9 , 15 17 ]. Since peripheral vasoconstriction may have an effect on both the AC and DC components of PPG, and the DC component may contain valuable information that has not been intensively explored, we hypothesized that autonomic responses induced by a noxious stimulus would decrease the AC component (reduced arterial pulsation) and increase the DC component (reduced venous and nonpulsatile arterial blood volume) of the PPG.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing increases and decreases in blood volume within a region of interest (ROI) enables extraction of heart rate and respiratory rate. The pulsatile PPG waveform can be used to monitor anesthesia depth [ 2 ], detect hypovolemia [ 3 ], detect arrhythmia [ 4 ], and approximate a patient’s blood pressure [ 5 ]. Recently, photoplethysmographic imaging (PPGI) has been developed as a noncontact method to measure spatial information of the pulsatile PPG waveform using a camera and incoherent source with near-homogeneous illumination to measure intensity in a reflectance geometry [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Ramsay sedation scale and CSI are indices monitoring the sedation extent during placement of tracheal tube to avoid the adverse events. 17 , 18 In the present study, we found that the Ramsay sedation score in P–H group was lower than that in P–D group, while the CSI was higher than that in P–D group, suggesting that P–H can maintain patients in more conscious and calm conditions to endure the placement of tracheal tube and undertake the sedation. The advantages of the P–H approach obviously meet well with the analgesia-based sedation and are favorable for the patients.…”
Section: Discussionmentioning
confidence: 41%